Frequency of Port Site Wound Infection in Laparoscopic Surgery - Javaid Sajjad Hashmi, Muhammad Tariq Khan, Raheel Imam Qureshi, Abdul Rasheed Zai, Muhammad Hanif Memon, Khumair Asif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the frequency of port site wound infection in laparoscopic surgery. Study Design: Retrospective study Place and Duration of Study: Department of Surgery, Rahbar Medical & Dental College, Lahore from 1st October 2020 to 30th September 2021. Methodology: One hundred cases of laparoscopic cholecystectomy were investigated. A standard protocol of National-Nosocomial Infections-Surveillance system as provided by CDC; was applied for identifying port site infection. Weeks assessment was initially done post 7 days of surgery in majority of patients and then after every 7 days for 4 weeks in those having port site infection formation. The demographic information was also documented using a well-designed questionnaire. Results: The age of the patients was between 25-63 years with a mean age of 35.4±2.5 years. There were 52% females and 48% males. Out of the total cases of port site infection 83% cases had epigastric port site infection. Conclusion: Laparoscopic surgery is associated with low risk of port site infection.